An Analysis Of Cash Flow Report Effect On Financial Performance (Case Study In Course And Training Institutions Putra Perwira Sukoharjo 2014-2016) - Supatminingsih, Sri; Setyawati, Setyawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
The purpose of this study is 1) To determine the effect of cash flow of operating activities partially to the financial performance at the Institute Course and Training Son Sukoharjo officers. 2) To know the effect of cash flow from investment activity partially to financial performance at Training Institute Institute and Training of Officer Sukoharjo. 3) To know the effect of cash flow from financing activities partially to financial performance at Training Institute Institute and Training of Officer Sukoharjo. 4) To determine the effect of cash flows from operating activities, cash flows from investment activities and cash flows from simultaneous financing activities to financial performance at the Course Institute and Training of Officers of Sukoharjo Officers. 5) To find out how much the cash flow effect of operating activities, the flow Cash from investment activities and cash flows from simultaneous financing activities to financial performance at the Sukoharjo Personnel Training Course and Training Institute. The object of this research is the institute's financial report and the training of sukoharjo officer's son. The sample in this study using financial report data while the period of data used in this study from monthly data from 2014 until 2016. Based on the results note that the operating variables have a partial significant influence on financial performance. This is evidenced by the value of tcount (0.176) greater than ttable (0.00075) or can be seen from the significance value of 0.045 ≤ 0.05. The investment variable has a significant influence on financial performance. This is evidenced by the investment variable tcount (0.103) greater than ttable (0.00075) or can be seen from the significance value of 0.026 ≤ 0.05. The funding variable has no significant partial effect on financial performance. This is evidenced by the financing variables tcount (0.003) is smaller than ttable (0.00075) or can be seen from the significance value 0.172 ≥ 0.05. Keywords: cash flow, financial performance